A method for preparing mixed slurry of lightweight board
By adjusting the raw material ratio and multi-stage foaming process, the problem of poor dispersion of light foam concrete slurry is solved, and the preparation of lightweight plates with high strength and good sound insulation and thermal insulation performance is achieved, ensuring the quality and performance of the plates.
Patent Information
- Application Number
- CN202211654304.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-12-22
AI Technical Summary
In the existing preparation methods for lightweight foam concrete, the difficulty of dispersion of the slurry leads to poor mechanical properties of the sheet, and the bubbles are prone to burst or dispersion unevenly, affecting the quality of the material.
By adjusting the raw material ratio and foaming process, the dispersion of ceramic granules and quartz sand is controlled, and the multi-stage foaming process is used to make the foam volume of polystyrene foaming material have a gradient to ensure that the slurry components are subjected to uniform force and avoid Settling and mixing are uneven.
The high strength and good sound insulation and heat insulation properties of lightweight boards are achieved, ensuring excellent dispersion of slurry, avoiding significant layering, and improving the quality of the boards.
Smart Images

Figure GDA0004253929580000121 
Figure GDA0004253929580000122 
Figure GDA0004253929580000131
Abstract
Description
Technical Field
[0001] The present application relates to a raw material for building materials, specifically a lightweight slurry, and more specifically a method for preparing a lightweight board mixed slurry. Background Art
[0002] Building panels can often be used as non-load-bearing walls during the construction of buildings. This type of panel is a type of prefabricated material. During the construction process, there is no need to cast it on site, only simple assembly is required. This can greatly shorten the construction period, reduce costs, and improve construction efficiency. At the same time, because it is a prefabricated part, it is less polluting to the environment.
[0003] In order to reduce the mass of prefabricated panels, thereby reducing the load-bearing capacity of the building, improving the sound insulation and thermal insulation performance of the building, and reducing the pollution of the environment by subsequent construction waste, we often use lightweight foam concrete to prepare the panels.
[0004] In the prior art, the invention patent application with publication number CN115304336A discloses that lightweight foamed concrete is prepared from the following raw materials in parts by weight: 40-70 parts of gel material, 20-40 parts of fly ash, 10-20 parts of fine sand, 10-20 parts of inorganic powder, 6-15 parts of modified glass fiber, 3-10 parts of foaming agent, 0.01-0.05 parts of foam stabilizer, and 0.1-2 parts of admixture. The present invention scientifically proportions and selects the raw materials for preparing foamed concrete, and helps the stable formation and uniform distribution of microporous foam by doping with two-step modified glass fiber, greatly improving the heat resistance and corrosion resistance of foamed soil, and the operation method is simple and convenient, and no pollutants are generated, which can greatly expand the application field of foamed concrete. In this scheme, H2O2, aluminum powder paste, and resin soap foaming agents are mainly used. The foaming agent is filled with gas in the slurry during the mixing process, and then a foam slurry with a porous structure is obtained, and a porous structure will be obtained during the slurry curing process. Although this type of foam concrete can reduce mass, the foam is porous and is produced by surfactants or substances that can generate gas, the bubble size is uniform and has poor mechanical properties.
[0005] In addition, there is a prior art, the invention patent with publication number CN113845349A discloses a process for preparing a lightweight foamed concrete with high compressive strength, wherein the lightweight foamed concrete with high compressive strength is made of composite concrete and a foaming agent, and comprises the following steps:
[0006] Step 1: Prepare composite concrete: first add water into the mixer of the hydraulic foaming machine, then put cement, fly ash, gypsum, water reducing agent and concrete reinforcing agent into the mixer and stir for 0.5min to 2min.
[0007] Step 2, preparing a foaming agent aqueous solution: mixing and stirring the foaming agent foam and water in a weight percentage of 1:25-1:40, thereby preparing a foaming agent aqueous solution.
[0008] Step 3: Prepare polystyrene foam: Add a foaming agent to the polystyrene resin and soften it by heating it inside a mixer to generate gas, thereby forming a polystyrene foam with a rigid closed-cell structure.
[0009] Step 4, preparing lightweight foamed concrete: first, placing the composite concrete and polystyrene foam into a stirring device for stirring and mixing. After mixing for 10 minutes, adding a foaming agent aqueous solution into the stirring device and stirring again for 5 minutes to prepare lightweight foamed concrete.
[0010] This solution uses a dual foaming material of polystyrene foam and foaming agent to prepare foam concrete. The foam is based on the introduction of air and polyethylene foam to jointly reduce the material mass. However, the mixture does not take into account the large volume of polystyrene and the light mass of air, making it difficult to predict the mixing of the slurry.
[0011] The present invention is based on the preparation method of foamed concrete in the prior art and the company's research on building materials. It is found that during the production process of the board, the slurry is difficult to disperse due to the excessive amount of lightweight substances in the concrete raw materials. It is intended to provide a proportioning and processing method to improve the mixing uniformity of such heterogeneous substances, obtain a uniformly mixed foam mixed slurry, and use the slurry to prepare building boards. Summary of the invention
[0012] The present invention is based on the prior art for the preparation of lightweight boards, which often involves adding substances that can generate bubbles, or substances that improve the surface activity of liquids, such as hydrogen peroxide, sodium dodecyl sulfate, etc. These substances can generate air or change the liquid surface properties of the slurry, thereby introducing bubbles, so that the solidified slurry forms a porous structure, thereby achieving the effect of reducing weight.
[0013] However, when preparing lightweight slurry in this way, bubbles are easily broken or the bubbles are unevenly dispersed, resulting in major problems in the mechanical properties of the prepared board.
[0014] Based on the problems in the prior art, the applicant intends to provide a method for preparing a mixed slurry for lightweight board materials. By comprehensively improving the ratio of raw materials and the production method of the slurry, the fluidity of the slurry is improved so that raw materials with different mass densities can be evenly mixed, and the prepared board materials have properties such as light weight and high strength.
[0015] Furthermore, one of the concepts of the present application is to provide a method for preparing a mixed slurry for a lightweight board material, wherein the slurry raw materials include at least polystyrene foam material, expanded clay, quartz sand, cement, and cement. The present application controls the weight of the expanded clay and then controls the dispersion of the expanded clay in the slurry according to the unit weight of the board material to be prepared, thereby achieving the effect of improving the quality of the board material.
[0016] In addition, one of the concepts of the present application is that, in a method for preparing a mixed slurry of a lightweight board material, we control the foaming process of the polystyrene foam material so that the foaming volume of the polystyrene has a certain gradient. Through the volume change of this gradient, the different components of the slurry are subjected to more uniform force after mixing, thereby avoiding uneven mixing caused by sedimentation of the slurry.
[0017] Specifically, the present invention provides a method for preparing a mixed slurry of a lightweight plate material, characterized in that it comprises the following steps:
[0018] Step S1, designing a raw material ratio according to the unit weight of the designed board slurry after drying, wherein the raw materials include polystyrene foam material, ceramsite, quartz sand, fiber, cement and water;
[0019] Step S2, foaming the polystyrene foam material;
[0020] Step S3, using water to regulate the quality of the ceramsite;
[0021] Step S4, blending the polyethylene foam material of step S2 with quartz sand, cement, and fiber and adding the remaining amount of water to obtain a mixed slurry A;
[0022] Step S5, adding the ceramsite obtained in step S3 into the mixed slurry A for stirring and blending to obtain a lightweight board mixed slurry.
[0023] In some embodiments, the unit weight range of the raw material ratio in step S1 is 48-100 kg / m 3 , preferably 52-80Kg / m 3 .
[0024] In the step S1, the polystyrene foam material comprises 10-30 parts, ceramsite 50-180 parts, quartz sand 20-30 parts, fiber 5-10 parts, cement 20-30 parts and water 30-60 parts by weight.
[0025] Furthermore, the foaming volume of the foaming material is 20-50 times;
[0026] Furthermore, the bulk density of the ceramsite is 300-700 kg / m 3, the preferred bulk density is 300-500Kg / m 3 .
[0027] Furthermore, the amount of the polystyrene foam material can be 10 parts, 20 parts, 25 parts, or 30 parts; the amount of the polystyrene foam material is preferably in the range of 10-25 parts, and more preferably 15-20 parts;
[0028] Furthermore, the amount of the ceramsite is preferably 60-150 parts, more preferably 80-150 parts;
[0029] Furthermore, the amount of quartz sand is preferably 25-30 parts;
[0030] Further, the amount of the fiber is 6-8 parts, more preferably 7-8 parts;
[0031] Furthermore, the cement is 22-28 parts, more preferably 25-28 parts.
[0032] In some embodiments, the mass ratio of the polystyrene foam material: ceramsite: quartz sand: fiber: cement is 1:6-10:1-1.5:0.2-1:1-1.5; the preferred mass ratio of the polystyrene foam material: ceramsite: quartz sand: fiber: cement is 1:8:1.2:0.5:1.4.
[0033] In some embodiments, the step of foaming the polystyrene foam material in step S2 includes dividing the polystyrene foam material into at least three parts and foaming the at least three parts of the polystyrene foam material using different foaming conditions.
[0034] Furthermore, the foaming temperature of the foaming condition is 60-90°C, preferably 70-80°C;
[0035] Furthermore, the foaming temperature of the foaming conditions may be one or more of 60-70°C, 70-80°C, 80-90°C;
[0036] Furthermore, the foaming time of the foaming conditions is 0.5-3h; preferably 1-3h;
[0037] More preferably, the foaming temperature of the foaming conditions can be one or more of 0.5-1h; 1-1.5h, 1.5-2h, 2-2.5h, 2.5-3h;
[0038] In some embodiments, the operation of using water to regulate the mass of the ceramsite in step S3 is to spray water onto the ceramsite to regulate the weight of the ceramsite.
[0039] Since ceramsite has a porous structure, it is easy to float above the slurry during stirring. At the same time, it is easy to absorb a large amount of liquid during the stirring of the slurry, resulting in uneven mixing of the slurry. In addition, the present invention uses moisture to adjust the weight of the ceramsite, on the one hand to regulate the water absorption of the ceramsite during mixing, and on the other hand to regulate its weight to prevent uneven mixing.
[0040] Furthermore, the weight of the ceramsite is regulated by foaming the polystyrene foam material in step S2.
[0041] In some embodiments, the operation of step S2 is to divide the polystyrene foam material into three equal parts, the first foaming condition is 0.5-1h, the foaming temperature is 70-80°C; the second foaming condition is 1-1.5h, the foaming temperature is 70-80°C; the third foaming condition is 2-3h, the foaming temperature is 70-80°C;
[0042] In step S3, 5-15 parts of water are used to control the mass of the ceramsite to adjust the bulk weight of the ceramsite to 300-400 kg / m 3 .
[0043] In some embodiments, the operation of step S2 is to divide the polystyrene foam material into three equal parts, the first foaming condition is 1-2 hours, the foaming temperature is 60-70°C; the second foaming condition is 1-2 hours, the foaming temperature is 70-80°C; the third foaming condition is 2-3 hours, the foaming temperature is 80-90°C;
[0044] In step S3, 5-15 parts of water are used to control the mass of the ceramsite to adjust the bulk weight of the ceramsite to 300-400 kg / m 3 .
[0045] In some embodiments, the operation of step S2 is to divide the polystyrene foam material into three equal parts, the first foaming condition is 0.5-1h, the foaming temperature is 60-70°C; the second foaming condition is 1-2h, the foaming temperature is 60-70°C; the third foaming condition is 1-2h, the foaming temperature is 70-75°C;
[0046] In step S3, 5-15 parts of water are used to control the mass of the ceramsite to adjust the bulk weight of the ceramsite to 500-600 kg / m 3 .
[0047] The main benefits of the present invention are embodied in the following aspects:
[0048] 1. Lightweight slurry is obtained by adjusting the ratio of raw materials, mainly by controlling the amount of lightweight materials, adhesives, aggregates, etc., so that the weight of the prepared slurry can be controlled within 48-100Kg / m3 The board has good sound insulation, heat insulation and high strength properties.
[0049] 2. Through the ratio of raw materials, especially the mass ratio of polystyrene foam material: ceramsite: quartz sand: fiber: cement is 1:6-10:1-1.5:0.2-1:1-1.5; the preferred mass ratio of polystyrene foam material: ceramsite: quartz sand: fiber: cement is 1:8:1.2:0.5:1.4. Within this range, the dispersibility of the slurry is better and no significant stratification phenomenon will occur.
[0050] 3. Through the adjustment of the process, especially the foaming process, the present invention adopts a variety of foaming processes, at least three foaming processes, so that the foaming volume of the prepared polystyrene foam material has significant differences. Then, the volume of expanded clay and quartz sand is combined to make the expanded clay, foaming material and other lightweight materials in the slurry evenly stressed, achieving a uniform dispersion effect. DETAILED DESCRIPTION
[0051] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] According to the present invention, a method for preparing a mixed slurry of a lightweight plate material is provided, characterized in that it comprises the following steps:
[0053] Step S1, designing a raw material ratio according to the unit weight of the designed board slurry after drying, wherein the raw materials include polystyrene foam material, ceramsite, quartz sand, fiber, cement and water;
[0054] In the step S1, the unit weight of the board slurry after drying can be 48-52 kg / m 3 ,52-58Kg / m 3 58-65Kg / m 3 ,65-72Kg / m 3 ,72-80Kg / m 3 ,80-90Kg / m 3 ,90-100Kg / m 3 ; The unit weight of the board slurry after drying is 48-100Kg / m 3 , preferably 52-80Kg / m 3 .
[0055] In the step S1, the polystyrene foam material comprises 10-30 parts, ceramsite 50-180 parts, quartz sand 20-30 parts, fiber 5-10 parts, cement 20-30 parts and water 30-60 parts by weight.
[0056] In some embodiments, the foaming volume of the foaming material is 20-30 times, 30-35 times, 35-40 times, or 40-50 times; the foaming range of the foaming material is 20-50 times, preferably 30-50 times.
[0057] Furthermore, the amount of the polystyrene foam material can be 10 parts, 20 parts, 25 parts, or 30 parts; the amount of the polystyrene foam material is preferably in the range of 10-25 parts, and more preferably 15-20 parts;
[0058] In some embodiments, the amount of the foaming agent can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts; the amount of the foaming agent can range from 10-30 parts, preferably 20-30 parts, more preferably 20-25 parts;
[0059] In some embodiments, the bulk density of the ceramsite is 300-700 Kg / m 3 , the preferred bulk density is 300-500Kg / m 3 ; The amount of ceramsite can be 50 parts, 60 parts, 70 parts, 80 parts, 100 parts, 150 parts, 180 parts; the amount of ceramsite ranges from 60 to 180 parts, preferably from 80 to 170 parts, and more preferably from 100 to 150 parts;
[0060] In some embodiments, the amount of quartz sand can be 20 parts, 25 parts, or 30 parts; the range of quartz sand can be 20-30 parts, preferably 25-30 parts;
[0061] In some embodiments, the amount of the fiber can be 5 parts, 7 parts, 8 parts, or 10 parts; the amount of the fiber is preferably in the range of 6-8 parts, and more preferably 7-8 parts;
[0062] In some embodiments, the amount of cement can be 20 parts, 25 parts, or 30 parts; the amount of cement is preferably in the range of 22-28 parts, and more preferably 25-28 parts.
[0063] In some embodiments, the mass ratio of the polystyrene foam material: ceramsite: quartz sand: fiber: cement is 1:6-9:1-1.7:0.2-1:1-1.7; the preferred mass ratio of the polystyrene foam material: ceramsite: quartz sand: fiber: cement is 1:7:1.4:0.5:1.6.
[0064] In some embodiments, the raw materials may further include a foaming agent and a surfactant;
[0065] The surfactant may be an alkyl sulfonate;
[0066] In some embodiments, a method for preparing a mixed slurry of a lightweight board material further includes the following steps: Step S2, foaming a polystyrene foam material;
[0067] In some embodiments, the foaming temperature of the foaming condition may be 60°C, 70°C, 80°C, 90°C; the foaming temperature range may be 60-90°C, preferably 70-80°C, more preferably 80-90°C;
[0068] Furthermore, the foaming temperature of the foaming conditions may be one or more of 60-70°C, 70-80°C, 80-90°C;
[0069] In some embodiments, the foaming time of the foaming conditions is 0.5h, 1h, 2h or 3h; the foaming time range can be 0.5-3h; preferably 1-3h; more preferably 2-3h.
[0070] More preferably, the foaming temperature of the foaming conditions can be one or more of 0.5-1h; 1-1.5h, 1.5-2h, 2-2.5h, 2.5-3h;
[0071] In some embodiments, a method for preparing a mixed slurry of a lightweight board material further includes the following steps: Step S3, using water to control the quality of the ceramsite;
[0072] Wherein, the step S3 is determined according to the foaming process of step S2;
[0073] Specifically, in some embodiments, the operation of step S2 is to divide the polystyrene foam material into three equal parts, the first foaming condition is 0.5-1h, the foaming temperature is 70-80°C; the second foaming condition is 1-1.5h, the foaming temperature is 70-80°C; the third foaming condition is 2-3h, the foaming temperature is 70-80°C;
[0074] In step S3, 5-15 parts of water are used to control the mass of the ceramsite to adjust the bulk weight of the ceramsite to 300-400 kg / m 3 .
[0075] In some embodiments, the operation of step S2 is to divide the polystyrene foam material into three equal parts, the first foaming condition is 1-2 hours, the foaming temperature is 60-70°C; the second foaming condition is 1-2 hours, the foaming temperature is 70-80°C; the third foaming condition is 2-3 hours, the foaming temperature is 80-90°C;
[0076] In step S3, 5-15 parts of water are used to control the mass of the ceramsite to adjust the bulk weight of the ceramsite to 300-400 kg / m 3 .
[0077] In some embodiments, the operation of step S2 is to divide the polystyrene foam material into three equal parts, the first foaming condition is 0.5-1h, the foaming temperature is 60-70°C; the second foaming condition is 1-2h, the foaming temperature is 60-70°C; the third foaming condition is 1-2h, the foaming temperature is 70-75°C;
[0078] In step S3, 5-15 parts of water are used to control the mass of the ceramsite to adjust the bulk weight of the ceramsite to 500-600 kg / m 3 .
[0079] In some embodiments, a method for preparing a mixed slurry of a lightweight board material further includes the following steps: step S4, blending the polyethylene foam material of step S2 with quartz sand, cement, and fiber and adding excess water to obtain a mixed slurry A;
[0080] In some embodiments, a method for preparing a mixed slurry for a lightweight board material further includes the following steps: Step S5, adding the ceramsite obtained in Step S3 to the mixed slurry A for stirring and blending to obtain a mixed slurry for a lightweight board material.
[0081] Example
[0082] The present invention will be further described below in conjunction with specific embodiments. The following embodiments are merely intended to illustrate the present invention rather than to limit it.
[0083] A method for preparing a mixed slurry of a lightweight plate material is provided, characterized in that it comprises the following steps:
[0084] Step S1, raw materials including polystyrene foam material, ceramsite, quartz sand, fiber, cement, water and surfactant;
[0085] Step S2, foaming the polystyrene foam material;
[0086] Step S3, using water to regulate the quality of the ceramsite;
[0087] Step S4, blending the polyethylene foam material of step S2 with quartz sand, cement, and fiber and adding the remaining amount of water to obtain a mixed slurry A;
[0088] Step S5, adding the ceramsite obtained in step S3 into the mixed slurry A for stirring and blending to obtain a lightweight board mixed slurry.
[0089] Example corresponding to Table 1
[0090] Table 1. Influence of raw material ratio
[0091]
[0092] Examples 1-5 use a traditional foaming process to prepare a mixed slurry for lightweight panels. This group of examples is designed to observe the effect of formula differences on the slurry, mainly by observing the slump change and appearance of the concrete slurry.
[0093] Table 2 Influence of slurry preparation process
[0094]
[0095]
[0096] The present Examples 6-11 are mainly used to verify the influence of the foaming process and the ceramsite treatment process on the slurry.
[0097] test
[0098] The obtained slurry is tested for its density and slump data;
[0099] The test results are as follows:
[0100] Table 3 Test results in the embodiment
[0101] Example 1 2 3 4 5 6 7 8 9 10 11 <![CDATA[Density / kg / m 3 > 850 1050 800 750 1250 850 860 860 870 870 870 Extension width / mm 650 630 600 550 620 690 710 710 670 720 720
[0102] From the test results, it can be seen that in the designs of Examples 1-5, the proportions of expanded clay, aggregate and cement in the mixed formula of the slurry will affect the density of the slurry and the flow properties of the slurry. Among the formulas used in the present disclosure, in Example 1 of the present disclosure design, its rheological properties are the best and it is most suitable as a slurry for lightweight panels.
[0103] In the test process, as can be seen from the tests of Examples 6-11, the pretreatment of ceramsite can greatly improve the flowability of the slurry, and the use of a multi-process foaming procedure for the foaming material can also greatly improve the flowability.
[0104] From the appearance aspect, we also found that for the multi-degree foaming process, the process can regulate the size of the foaming agent to a certain extent, which in turn can affect the material distribution in the slurry and affect the fluidity.
[0105] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a mixed slurry of a lightweight plate material, characterized in that: The following steps are involved: Step S1, designing a raw material ratio according to the unit weight of the designed board slurry after drying, wherein the raw materials include polystyrene foam material, ceramsite, quartz sand, fiber, cement and water; Step S2, foaming the polystyrene foam material; Step S3, spraying water on the ceramsite to control the quality of the ceramsite; Step S4, blending the polyethylene foam material of step S2 with quartz sand, cement, and fiber and adding the remaining amount of water to obtain a mixed slurry A; Step S5, adding the ceramsite obtained in step S3 to the mixed slurry A for stirring and blending to obtain a lightweight board mixed slurry; In step S1, the unit weight range of the raw material ratio is designed according to the unit weight of the board slurry after drying, and the unit weight range is 48-100Kg / m 3 ; In the step S1, the polystyrene foam material comprises 10-30 parts, ceramsite 50-180 parts, quartz sand 20-30 parts, fiber 5-10 parts, cement 20-30 parts and water 30-60 parts by weight; The foaming volume of the foaming material is 20-50 times; The bulk density of the ceramsite is 300-700 Kg / m 3 ; The step of foaming the polystyrene foam material in step S2 includes dividing the polystyrene foam material into at least three equal parts and foaming the polystyrene foam material divided into at least three equal parts using different foaming conditions; The foaming temperature of the foaming condition is 60-90°C; The foaming time of the foaming conditions is 0.5-3h; In the step S3, 5-15 parts of water are used to control the quality of the ceramsite.
2. A method for preparing a mixed slurry of a lightweight board material as claimed in claim 1, characterized in that: The mass ratio of the polystyrene foam material: ceramsite: quartz sand: fiber: cement is 1:6-10:1-1.5:0.2-1:1-1.
5.
3. A method for preparing a mixed slurry of a lightweight board material as claimed in claim 2, characterized in that: The operation of step S2 is to divide the polystyrene foam material into three equal parts, the first foaming condition is 0.5-1h, the foaming temperature is 70-80℃; the second foaming condition is 1-1.5h, the foaming temperature is 70-80℃; the third foaming condition is 2-3h, the foaming temperature is 70-80℃.
4. A method for preparing a mixed slurry of a lightweight board material as claimed in claim 2, characterized in that: The operation of step S2 is to divide the polystyrene foam material into three equal parts, the first foaming condition is 1-2h, the foaming temperature is 60-70℃; the second foaming condition is 1-2h, the foaming temperature is 70-80℃; the third foaming condition is 2-3h, the foaming temperature is 80-90℃.
5. A method for preparing a mixed slurry of a lightweight board material as claimed in claim 2, characterized in that: The operation of step S2 is to divide the polystyrene foam material into three equal parts, the first foaming condition is 0.5-1h, the foaming temperature is 60-70°C; the second foaming condition is 1-2h, the foaming temperature is 60-70°C; the third foaming condition is 1-2h, the foaming temperature is 70-75°C.
Citation Information
Patent Citations
Preparation process of light foam concrete with high compressive property
CN113845349A
Heat-resistant and corrosion-resistant lightweight foam concrete and preparation method thereof
CN115304336A
Cast-in-situ construction method of composite foaming slurry
CN102909787A
Polystyrene cement compound thermal insulation material and preparation method thereof
CN106187311A
Ceramsite concrete and preparation method thereof
CN110229018A